The effect of subsidized childcare on female labor market participation in Costa Rica - Quirós, Aníbal Jesús (2020)
In this study, we estimate the effects of the use of subsidized childcare on the probability of female participation in the labor market and on the numbers of hours worked in Costa Rica. We use household surveys and a combination of econometric techniques in order to control for potential bias. We find that females that belong to beneficiary households have between 9 and 14 additional percentage points in the probability to participate in the labor force. They also worked between 8 and 19 percent more than females that are not in the program. The effects on labor participation are larger for women that have not finished high school. The effects on the numbers of hours worked are larger for those in the poorest quintile. These results suggest that the expansion of this program can contribute to reduce the labor participation gender gap, which is larger among the poor. This, in turn, could lead to important reductions in poverty levels.